Pertanggungjawaban Pidana dalam Kasus Korupsi Tata Kelola Minyak Pertamina Tahun 2025 - Lintang Sayyidina; Anza Ronaza Bangun (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
Oil and natural gas are vital resources for the state, and their management must be carried out carefully and transparently. However, the complexity of existing management is often exploited by irresponsible parties to commit corruption that harms state finances. This study aims to analyze how criminal law regulates the accountability of perpetrators in the oil management corruption case at Pertamina in 2025. The method used is normative juridical, by reviewing laws and regulations regarding corruption, state-owned enterprises (BUMN), and related legal literature. The results of the study indicate that criminal liability in this case is not only directed at individual officials, but also corporations or companies. This is because the element of mens rea (malicious intent) was found in the act. Therefore, law enforcement must focus more on recovering state losses and improving Pertamina's internal oversight system, rather than simply imprisoning the perpetrators.